Bridging Religiosity and Digital Competence: The Mediating Role of Digital Ethics in Higher Education - Lina Rifda Naufalin; Cicilia Dyah Sulistyaningrum Indrawati; Mintasih Indriayu; Leny Noviani (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
Digital competence is essential to teacher professionalism in the 21st century, yet few have examined how religiosity shapes it through digital ethics, particularly in Islamic higher education. To fill this gap, the research uses a quantitative survey approach to investigate the mediating role of digital ethics between religiosity and digital competence among pre-service teachers. The sample of 164 students of the social and humanities field education study program at Islamic universities in Java Island, Indonesia was obtained by purposive sampling method. Data analysis was conducted using the PLS-SEM method to test the direct and indirect effects between variables. The results shows that religiosity positively and significantly influenced digital ethics (t = 11.351; f² = 1.232) and digital competence (t = 2.066; f² = 0.035). Digital ethics also strongly predicted digital competence (t = 12.543; f² = 0.958). The indirect test confirmed that religiosity influenced digital competence through digital ethics (t = 7.832), with an overall R² = 0.738, indicating a strong predictive model. This finding confirms that internalizing religious values through digital ethics learning can strengthen students’ digital competence. Theoretically, this study extends digital competence theory by incorporating moral and spiritual dimensions through the lens of Bandura’s social cognitive theory. The study urges Islamic higher education institutions to integrate these values into practice-based curricula, such as microteaching, to develop digital competencies that are both technically proficient and ethically grounded.